Risk of suicide after a diagnosis of sleep apnea: A nationwide longitudinal study. (May 2023) - Chu, Che-Sheng; Huang, Kai-Lin; Bai, Ya-Mei; Su, Tung-Ping; Tsai, Shih-Jen; Chen, Tzeng-Ji; Hsu, Ju-Wei; Liang, Chih-Sung; Chen, Mu-Hong
Abstract: Previous studies have presented evidence on the association between sleep apnea and suicidal ideation and planning, but the relationship between a clinical diagnosis of sleep apnea and suicide attempts remains unknown. We investigated the risk of suicide after a diagnosis with sleep apnea using data from a nationwide community-based population database, i.e., the Taiwan National Health Insurance Research Database. We recruited 7, 095 adults with sleep apnea and 28, 380 age-, sex-, and comorbidity-matched controls between 1998 and 2010 and followed them up until the end of 2011. Individuals who exhibited any (once or repeated) suicide attempts were identified during the follow-up period. The E value was calculated for unmeasured bias. Sensitivity analysis was conducted. Patients with sleep apnea were more likely to carry out any suicide attempt (hazard ratio: 4.53; 95% confidence interval: 3.48–5.88) during the follow-up period than the controls after adjusting for demographic data, mental disorders, and physical comorbidities. The hazard ratio remained significant after excluding individuals with mental disorders (4.23; 3.03–5.92). The hazard ratio was 4.82 (3.55–6.56) for male patients and 3.86 (2.33–6.38) for female patients. Consistent findings of increased risk of repeated suicide attempt were found among patients with sleep apnea. No association was found between continuous positive airway pressure treatment and suicide risk. The calculated E values support suicide risk after the diagnosis of sleep apnea. The risk of suicide was 4.53-fold higher in patients diagnosed with sleep apnea than in their counterparts without sleep apnea.